2023
DOI: 10.1101/2023.06.02.543338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the genomic landscape of multidrug resistance inPlasmodium falciparumand its impact on parasite fitness

Abstract: Drug-resistant Plasmodium falciparum parasites have swept across Southeast Asia and now threaten Africa. By implementing a P. falciparum genetic cross using humanized mice, we report the identification of key determinants of resistance to artemisinin (ART) and piperaquine (PPQ) in the dominant Asian KEL1/PLA1 lineage. We mapped k13 as the central mediator of ART resistance and identified secondary markers. Applying bulk segregant analysis, quantitative trait loci mapping and gene editing, our data reveal an ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…At present, a well-established correlation between pfhrp2/3 deletions and pfk13 mutations, as well as their collective impact on parasite fitness, remains unclear. In vitro experimentations have indicated that the pfk13 C580Y mutation entails modest fitness costs when accompanied by multicopy pm2/3 , while it remains fitness-neutral in the presence of single pm2/3 copies 30 . We hypothesise a comparable scenario of fitness cost interplay between pfk13 mutations and pfhrp2/3 deletions.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a well-established correlation between pfhrp2/3 deletions and pfk13 mutations, as well as their collective impact on parasite fitness, remains unclear. In vitro experimentations have indicated that the pfk13 C580Y mutation entails modest fitness costs when accompanied by multicopy pm2/3 , while it remains fitness-neutral in the presence of single pm2/3 copies 30 . We hypothesise a comparable scenario of fitness cost interplay between pfk13 mutations and pfhrp2/3 deletions.…”
Section: Discussionmentioning
confidence: 99%